Bauji Shallot Variety (Allium ascalonicum L.) Growth Respond And Yield After Kirinyuh Plant Methanol Extract (Chromolaena odorata L.) Treatment - Lena Dian Saputri; Zulfa Zakiah; Elvi Rusmiyanto; Pancaning Wardoyo (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2022)
It is crucial to improve the shallot (Allium ascalonicum L.) cultivation system on peatlands to increase the growth and production of shallots. One is the provision of Biostimulants derived from Kirinyuh (Chromolaena odorata L.) extract. This study aimed to determine the effect of Kirinyuh (C. odorata) methanol extract on the growth and yield of shallot (A. ascalonicum) and to determine the best concentration and application time of Kirinyuh extract to increase the growth and yield of shallots. This research was conducted from September to December 2020 at the Biology Laboratory and Greenhouse Department of Biology, Faculty of Mathematics and Natural Sciences, Tanjungpura University, Pontianak. The study used a completely randomized (CRD) factorial pattern with two factors. The first factor was the concentration of Kirinyuh extract, which consisted of 5 treatments (0; 25; 50; 75, and 100 mg/L), and the second factor was application time which consisted of 2 treatments (1 week and two weeks). The results showed that the combination of Kirinyuh extract concentration and application time had a significant effect on wet shoot weight, dry shoot weight, tuber quantity, wet tuber weight, and tuber dry weight but had no significant effect on plant height, number of leaves, wet weight of roots, dry weight, root and tuber diameter. The concentration of Kirinyuh extract and the best application time was 100 mg/L with an application time of 2 weeks.